Effect of a herbal drink on cycling endurance performance - Singh, Rabindarjeet; Sirisinghe, Roland G. (2001)
The aim of this study was to evaluate the effects of 'AgroMas®' herbal drink on physiological responses and endurance performance during cycling exercise. Nine cyclists cycled on a cycle ergometer at 71.9±0.7% of the maximal oxygen consumption (V02max) until exhaustion in a room maintained at 23.9±0.2°C and 64.7±1-.5 % relative humidity on two occasions with 1-week interval. The point of exhaustion was defined as the time when subjects could no longer maintain 40 RPM. Subjects ingested either a 'herbal drink'(H) or placebo(P). During each exercise bout, subjects received 3ml.kg-1 body weight of H or P every 20 minutes in a double-blind randomised study design. Blood samples were collected at rest and during exercise, every 20 min, for the determination of substances. Total cycling time to exhaustion was insignificantly (p > 0.05) longer with H (83.7±4.6 min) than P-(B1.5±5.0 min). Changes in body weight, oxygen uptake, plasma volume, core temperature,skin temperature,heart rate,perceived rate of exertion,fluid sensation,respiratory exchange ratio,blood glucose concentration and blood lactate concentration were similar with both H and P treatment. These results showed that the H and P treatment elicited similar exercise performance, thermoregularity and physiological responses during endurance cycling. Thus, it can be concluded that the 'AgroMas®'herbal drink could not enhance cycling endurance performance.